KEMARITIMAN INDONESIA: SEBUAH KAJIAN KRITIS - Wahyu Wibowo (Institut Transportasi dan Logistik Trisakti, 2017)
The purpose of this paper is to examine the vision of Indonesia as a maritime axis of the world. This vision is important, in addition to its worldwide scale content, and also directly addressed by the President of the Republic of Indonesia Joko Widodo at the East Asia Summit in Nay Pyi Taw, Myanmar on November 13, 2015. This vision is increasingly important because there are still many of our marine problems, particularly those relating to security and economic issues, are suspected to weaken that vision. Using heuristic technique and eclectic method, philosophical study of this qualitative descriptive type will center on the President's speech and the national newspaper coverage of maritime problems, which likely raises the ethical problems of nation and state. As a result, Indonesia's vision as a maritime axis of the world should be manifested with a critical note.